Pembagian Harta Warisan Ditinjau dari Kitab Undang-Undang Hukum Perdata - Ni Luh Gede Suwarni; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
Indonesia has experienced rapid development from ancestral ages to modern ages in terms of its people living with daily-supporting facilities. In other words, the Indonesian people live with a legacy which is then developed. Regarding inheritance, this study examines two legal issues: (1) distribution of inheritance according to the Civil Code and (2) settlement of disputes over distribution of inheritance results according to the Civil Code. This study was designed using a normative legal research method design; the data were collected by applying note-taking and analysing techniques based on legal materials. Based on the results of data analysis, it is found that in terms of its form there are three types of rights and obligations of an heir: openbaar testament, a form of inheritance made by a notary, in which case, the person who will transfer the inheritance appears before a notary and declares his will; olographis testament, a form of inheritance realising in writing by hand and is affixed by the hand of the inheritor (elgenhading / gedepoecerd); and a secret testament, a form of inheritance that requires the transfer of inheritance by written evidence, made by the person transferring the inheritance but not necessarily handwritten. There are two forms of dispute resolution related to inheritance through litigation, namely the general court, which in this case is the district court, the authority to examine disputes and the commercial court of a special court that is within the environment of a general court that has the competence to examine and decide an application for participation and postponement of debt payment obligation (PKPU) and disputes over intellectual property rights (HaKI).